Determinants of project management success: view from an emerging economy - Muhammad Ashraf, Fauzi; Khairul Firdaus, Anuar; Rahimi, A. Rahman; Jamaludin, Jupir; Noraina Mazuin, Sapuan (Emerald Publishing Limited, 2023)
Purpose: Achieving project success is the goal of every project. Due to various project requirements, some of the key determinants of project success cannot be met. The purpose of this paper is to understand relying factors that can lead to a successful project that includes project management maturity, decision-making, coordination and knowledge management. Design/methodology/approach: A self-administered survey was distributed to 231 project managers in the Malaysian project management community. Analysis using partial least square structural equation modelling was applied in testing the proposed relationship between these latent variables. Findings: Finding shows that all the hypotheses were supported and significant. The most impactful factor is project management maturity, followed by knowledge management. Practical implications: Implication to the project management industry includes providing autonomy to individuals involved in their expertise and management of efficient cross-functional teams between teams in the project. A systematic knowledge management system through a central repository would contribute to the efficient and flexible distribution of knowledge throughout the project process. Originality/value: This study is one of the few studies focussing on determinants of project success in Malaysia.